The Influence of Transformational Leadership and Communication with Motivation as an Intervening Variable on the Performance of Tourism Village Managers in Ubud District, Gianyar Regency - I Gede Agus Ari Eka Budi Pratama; Ida Ayu Putu Widani Sugianingrat; Putu Herny Susanti (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
The tourism village as one of the tourist destinations developed by the village community, especially in Ubud District, Gianyar Regency, is managed by Pokdarwis. For this reason, managers are required to provide the best performance in advancing tourism villages. The purpose of this study was to determine and analyze the effect of transformational leadership and communication with motivation as an intervening variable on the performance of tourism village managers in Ubud District, Gianyar Regency. The research population is all the administrators or Pokdarwis members of tourist villages in Ubud District as many as 110 people. The sampling technique used purposive sampling in order to obtain 93 people as respondents. The method of analysis using descriptive analysis and inferential analysis with SEM-PLS analysis. The results show that directly transformational leadership, communication and motivation have a positive and significant effect on the performance of managers, transformational leadership and communication have a positive and significant effect on motivation, and motivation is positively and significantly able to mediate the influence of transformational leadership on the performance of Tourism Village managers in Ubud District. Gianyar Regency. The implication of the research is the need to improve harmonious relationships between Pokdarwis members as tourism village managers to participate together in developing a better tourist village.